2019
DOI: 10.3390/ijms20071525
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Particle Shapes on the Field-Dependent Rheological Properties of Magnetorheological Greases

Abstract: The transient response of magnetorheological (MR) materials, in general, is very important for design consideration in MR-based devices. Better response to magnetic fields is beneficial for a better response rate to the electrical current applied in the electromagnetic coil. As a result, MR-based devices would have a high response to external stimuli. In this work, the principal characteristics of magnetorheological greases (MRGs) which have two different particle shapes are experimentally investigated. One ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 52 publications
3
4
0
Order By: Relevance
“…The facilitated movement was theorized to result in stronger CIP chains, which increased resistance. The results obtained in this part of the study were validated by comparing it with previous studies [13], [14]. After 1 year, the storage modulus obtained is shown in Figure 6.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…The facilitated movement was theorized to result in stronger CIP chains, which increased resistance. The results obtained in this part of the study were validated by comparing it with previous studies [13], [14]. After 1 year, the storage modulus obtained is shown in Figure 6.…”
Section: Resultssupporting
confidence: 75%
“…The breaking down of MRG, as stated in the previous studies [12]- [14], was a strong indication of grease degradation. Several studies have established the degradation of grease in various conditions, including high temperature [9], repeated shear [15], and even decomposition due to electrical discharge [16].…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…The first and second additional data were taken from [15] of the spherical and plate-like data, respectively, with total data points of about 90. In terms of training accuracy, the R 2 value of 1 has shown almost the same result with data 2 [47]. In terms of testing accuracy, the prediction based on additional data can produce better accuracy than the model based on data 2.…”
Section: Input Selectionmentioning
confidence: 61%
“…Pan et al [20] showed that the non-magnetic material on the surface increased the spacing between the magnetic particles, so the magnetic properties of the composite particles will be weaker than before the coating. Therefore, it can be seen from figure 7 that the magnetorheological shear stress of the CDS type EMRF is smaller than that of the CI type in the range [0, 1.8]A and significantly smaller than that of the Fe 3 O 4 type in [0, 1]A. Mohamad et al [23] showed that a MRF prepared with complex-shaped magnetic particles has greater magneto-rheological shear stress than that prepared with smooth spherical magnetic particles. The irregular shape increases the friction between the magnetic particles, which can improve the structural strength of the magnetic chain.…”
Section: Discussionmentioning
confidence: 97%